(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluate the nutritional status of children aged 6 - 24 months and some factors related to malnutrition at the Nutrition Clinic in 2023. Subjects and methods: The study was a descriptive cross-sectional study on 190 children 6 - 24 months and their mothers from January 1, 2023 to September 30, 2023. Results: The majority of children with stunting are 21.6%. Types of malnutrition tend to increase with age group. The deficiency rates of iron, zinc, vitamin D and calcium are 26.3%, 22.1%, 20.5%, and 20%. Early complementary feeding and no weight tracking was related to underweight. Conclusions: Guide for mothers extra micronutrient and update knowledge and correct practices on child care to reduce the risk of malnutrition.